Development of reading ability is facilitated by intensive exposure to a digital children's picture book - 正高 信男 (Frontiers in Psychology, 2014)
デジタル絵本に独自の教育効果を発見 -4歳児、ひらがなの読みを促進-. 京都大学プレスリリース. 2014-05-02. Here the author presents preliminary evidence supporting the possibility that the reading ability of 4-year-old children can be improved as a consequence of intensive exposure to the narrative in a digital picture book over a consecutive 5-day period. When creating the digital version used here, two additional functions were provided with it. First, the entire story was voice-recorded by a professional narrator and programmed so that it was played as narration from the speaker of an iPad. Next, as the narration of each digitized page proceeded, the character exactly corresponding to that pronounced by the narrator at that moment became highlighted in red. When the subjects' literacy capability with respect to the syllabic script of the Japanese language (kana) was evaluated before and after the exposure, their performance score was found to increase after the exposure to the digital book, whereas such a change was not recorded in children who experienced exposure to the printed version of the same picture book read to them by their mother. These effects were confirmed when the children were retested 4 weeks later. Although preliminary, the current study represents the first experimental evidence for a positive effect of exposure to digital books upon any aspect of child development.